2017
DOI: 10.1097/ico.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

Descemet Membrane Thickening as a Sign for the Diagnosis of Corneal Graft Rejection: An Ex Vivo Study

Abstract: Purpose To disclose, using an ex vivo study, the histopathological mechanism behind the in vivo thickening of the Endothelium/Descemet’s membrane complex (En/DM) observed in rejected corneal grafts (RCGs). Methods Descemet’s membrane (DM), endothelium (En), and retrocorneal membranes (RCM) make up the total En/DM thickness. These layers are non-differentiable by HD-OCT; therefore, the source of the thickening is unclear from an in vivo perspective. A retrospective ex vivo study (from September 2015 to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…There is a strong evidence in the literature that measuring the thicknesses of corneal microlayers in vivo is valuable for the diagnosis of numerous corneal diseases, such as Fuchs dystrophy, keratoconus, and corneal graft rejection 4,5,1215. Those studies have shown excellent potential in the diagnosis of these pathologies using thickness of corneal microlayers, but they have also disclosed limitations in the technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a strong evidence in the literature that measuring the thicknesses of corneal microlayers in vivo is valuable for the diagnosis of numerous corneal diseases, such as Fuchs dystrophy, keratoconus, and corneal graft rejection 4,5,1215. Those studies have shown excellent potential in the diagnosis of these pathologies using thickness of corneal microlayers, but they have also disclosed limitations in the technology.…”
Section: Discussionmentioning
confidence: 99%
“…There are six interfaces between the corneal microlayers, namely, the air-epithelium interface (EP), the basal-epithelial interface (BS), the epithelium-Bowman's interface (BW), the Bowman's-stroma interface (ST), the DM, and the endothelium-aqueous interface (EN). Measuring the thicknesses of those microlayers in vivo has proven to be valuable for the diagnosis of various corneal diseases, such as Fuchs dystrophy, keratoconus, corneal graft rejection, and dry eye 4,5,1215. For example, thinning of Bowman's microlayer has been shown to be an accurate sign for the diagnosis of keratoconus 4,16.…”
Section: Introductionmentioning
confidence: 99%
“…OCT assessment of the tear meniscus has been extensively studied during the last 10 years [32]. The pathophysiology of dry eye disease is characterized by instability of the pre-corneal tear film along with increased osmolarity and ocular surface inflammation and damage [33].…”
Section: Dry Eye and Tear Evaluationmentioning
confidence: 99%
“…OCT meniscometry solves this problem by continuously measuring the tear film, using a tear meniscus to represent the total volume. This method of acquiring images is objective, non-invasive and rapid [32,34]. However, data analysis is complex, operator-dependent and time-consuming [36].…”
Section: Dry Eye and Tear Evaluationmentioning
confidence: 99%
See 1 more Smart Citation